Analyzing the Impact of Workload and Emotional Intelligence on the Performance of Air Traffic Controllers with Commitment as an Intervening Variable at the Perum LPPNPI MATSC - Puspita, Farahgisa Loranti; Kadir, Abd Rahman; Umar, Fauziah (The Scientia Journal of Financial issues, 2022)
Every business and company has objectives that must be accomplished. In order to attain these goals, it is essential for all components of the organization to collaborate effectively, with human resources (HR) serving as one of the instrumental tools employed by the company. This study seeks to examine the potential impact of workload and emotional intelligence on the performance of Air Traffic Controllers, with commitment serving as an intervening variable. This study employs a quantitative approach to examine the causal link between variables and evaluate the notion of their interconnections. Data was collected by distributing questionnaires to 100 respondents and the collected data was processed using the SmartPLS 4 program. The data analysis indicates that the workload and work commitment of ATC at Perum LPPNPI MATSC Branch have a substantial impact on its performance. Additionally, emotional intelligence also affects ATC performance, although to a lesser extent compared to workload and work commitment. According to the data collected, Commitment is the most influential variable in determining performance. The path coefficient is 0.77, with a p-value of 0.000, and a 95% confidence interval ranging from 0.553 to 0.928. The f-square value is significantly high, measuring 0.735. This variable exerts a significant impact on performance